2022
DOI: 10.1186/s12906-022-03709-8
|View full text |Cite
|
Sign up to set email alerts
|

Proportion and associated factors of the utilisation of complementary and alternative medicine exclusively in a hospital in Bangladesh

Abstract: Background Complementary and alternative medicine (CAM) has played a critical role in ensuring universal access to basic health care services around the world. In Bangladesh, conventional medicine is a common approach for health care practices, yet, due to Bangladesh’s high out-of-pocket payment, millions of people utilise CAM-based healthcare services for illnesses. In Bangladesh, there is a scarcity of data on how CAM is perceived and utilised. The goal of this study was to determine the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…On the other hand, other studies reported that younger adults had a higher prevalence of using CAM, and that women mostly used CAM. A previous Bangladeshi study revealed that 60.6% of patients of age 26 to 45 years old used CAM, which was the highest figure of all age groups, and 39.8% of female participants used CAM for treatment (Shahjalal et al, 2022b).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…On the other hand, other studies reported that younger adults had a higher prevalence of using CAM, and that women mostly used CAM. A previous Bangladeshi study revealed that 60.6% of patients of age 26 to 45 years old used CAM, which was the highest figure of all age groups, and 39.8% of female participants used CAM for treatment (Shahjalal et al, 2022b).…”
Section: Discussionmentioning
confidence: 87%
“…Along with these, media influence, better performance from CAM, and poor results from modern medicine were also common influential factors in using CAM. The study in Bangladesh reported that 55.5% of patients used CAM because of its less adverse effects and 41.6% of patients utilised it for its effective disease management (Shahjalal et al, 2022b). In India, patients used CAM because of its effectiveness (50%), advice from family (43%), and on-time usage on illness (51%) (Roy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation